LAND MARKET AS THE SEGMENT OF THE REAL PROPERTY MARKET - Тітова, С.; Бабенко, О. (Bulletin of Taras Shevchenko National University of Kyiv. Military-special sciences, 2018)
Analysis of the current state of the land market in the agrarian sector of the economy through the implementation of land reform is carried out.. The objective foundations and content of the institutional mission of the state in the land market, which are determined by the specific characteristics of real estate, are revealed. The preconditions for forming the land market in Ukraine are analyzed and the possible consequences of the introduction of free circulation of agricultural land are determined. A conceptually new direction of the land market study is proposed, which is to reveal the essence of the land as an independent economic category and the forms of its functioning in a particular segment of the market real estate, the inversion character of the land market formation is grounded, and the triple logic of land entry into market turnover is revealed. Keywords: agrarian sector of economy, landmark, non-profit markets, land reform, land lease, land rent, land loan.